Compartimentalización de la biomasa aérea de Grevillea robusta A. en función a la densidad inicial de plantación = Aboveground biomass allocation of Grevillea robusta A. based on initial planting density - Barth, Sara Regina; Giménez, Ana María; Joseau, Marisa Jacqueline; Gauchat, Maria Elena; Fassola, Hugo Enrique (2018)
Planting density at a given age is a reliable indicator of the degree of a site’s arboreal cover and thus it represents the structure of the forest stand. The objective of this paper was to assess the initial planting density’s effect on aboveground biomass accumulation in an 18-year old Grevillea robusta plantation. The test was conducted in Posadas, Misiones (Argentina), with 4 initial planting densities (162, 375, 750 and 1500 plants/ha). Biomass accumulation was analyzed in the shrub, herbaceous, forest floor and trees strata (leaves, branches, stem and bark). In the case of trees, the effects of the treatments were studied in individuals and in the stands. The total understory biomass presented significant differences among treatments. Biomass allocation varied leading to a higher presence of dead branches and shrub biomass at higher planting densities. The herbaceous stratum had a higher biomass accumulation with the lowest planting density treatment. Larger spacing resulted in larger individual diameter but the highest stem biomass accumulation per hectare was observed with the smallest spacing.